Cationic polymerization of isobutylene catalysed by AlCl3 with multiple nucleophilic reagents. Issue 100 (13th October 2016) - Zhu, Shan; Lu, Yangcheng; Wang, Kai; Luo, Guangsheng
Abstract : Adding the multiple nucleophilic reagents, iPr2 O and EB, in the initiation system is an effective way to attain the controlled polymerization of isobutylene. Abstract : In this work, by exploiting the perfect performances of microflow reactors in mixing and residence time control, we systematically investigated the cationic polymerization of isobutylene (IB) catalysed by AlCl3 with multiple nucleophilic reagents, isopropyl ether (iPr2 O) and ethyl benzoate (EB). Through properly introducing iPr2 O and EB, the polymerization of IB could produce PIBs with a narrow molecular weight distribution (PDI < 2.0), a relatively high molecular weight (>40 000 g mol −1 ), and a high content of exo -olefin ( w > 70%) at relatively high temperatures (−30 °C), during which most of the monomer conversion (>70%) could be fulfilled within 0.5 s and the chain scission mainly takes place after seconds. The expression [2[EB] + [iPr2 O]]/[AlCl3 ] being equal to 1 is recognized as a quantitative criterion for achieving these outcomes, corresponding to H + iPr2 OAlCl3 (OH) − initiating polymerization with inhibited chain transfer by introducing EB(AlCl3 ) n, but eliminating free AlCl3 . Increasing the flow capacity in a certain microflow system provides the potential to increase the molecular weight further and facilely tailor it for particular applications. This work verifies the various functions of multiple nucleophilic reagents and their ability to break the trade-off of conversion rate and propagation chain stability in cationic polymerization and develop new functional products of PIBs.